Hubungan Antara Kelainan Siklus Menstruasi Dengan Kejadian Akne Vulgaris Pada Santriwati Sma Islam Terpadu Nur Hidayah Kartasura - Dwi Utami Siregar, Ersi; , dr. Flora Ramona Sp, Sp.KK., M.Kes; , dr. Listiana Masyita Dewi (2016)
Background: Acne vulgaris (AV) is an inflammatory skin disease that comes from pilosebacea follicle. The largest incident occures at age 14-17 years old women, 16-19 years old men. The presence of AV was related with increased rate of sebum production by androgen hormone as well as estrogen and progesterone hormones could trigger the AV before menstruation. Limited data suggest that AV are more pronounced in adolescent with menstrual cycle disorder. Purpose: The aim of this study is to know about the relationship between menstrual cycle disorder with existence AV. Method: This study is an observational analytic research with cross sectional design. The study population was santriwati of SMA-IT Nur Hidayah Kartasura aged 15-18 years old who had already started menstruating. The selection of respondens with a simple random sampling method obtained 55 respondents. Primary data were collected through questionnaire and face photo of respondents. Test analysis used chi square. Result: The result of statistical test using chi square is p-value= 0,103 (p>0,05). There was a higher incidence of normal menstrual cycle with AV (43,6%) just than 30,9% student had menstrual cycle disorder with AV in our study. Conclusion: This study concluded that there is no significan relationship between menstrual cycle disorder with AV to the students of SMA-IT Nur Hidayah Kartasura.